The Relationship between Financial Market Volatility and Macroeconomic Indicators - Jena , Dr. Duryodhan; Ghosh , Dr. Moli; Haripriya , V.; Bhatnagar, Sanjay; Sharma, Divya; Rashmi; Agarwal , Dr. Varsha (International Journal of Accounting and Economics Studies, 2025)
Economists and experts in finance have recently focused more on the connection between the stock market and the actual economy. Indeed, it is difficult to envision a world without stock markets currently. The operations in the stock markets and their connections to the macro economy have taken on a great deal of significance in the current situation, which is characterized by the growing interconnectedness of the financial markets and the execution of different stock market reform measures. This research aims to investigate the relationship between stock prices and several carefully chosen macroeconomic indicators. Before that, it's critical to appreciate the significance of the nation's stock market and stock prices. According to financial theorists, the share price is calculated by dividing the number of outstanding shares by the present value of all projected future earnings for the company. This implies that price is determined by the company's earning potential. Additionally, the market's estimate of a company's earnings potential is influenced by several elements, including the possible earnings in the future, the potential growth, and the time it will take to achieve those goals. All available information about a firm and its potential for future profitability is reflected in its price. Prices fluctuate as information about a company's future becomes available to the public. But future uncertainty can increase volatility, and psychological variables can intensify the impact of fresh knowledge.